XIX ÁSIR QARAQALPAQ LIRIKASÍNDA TÁRIYP JANRÍNÍŃ KÓRKEM AWIZEKI DEREKLERI - Djangabaeva, H. (SCIENCE and SOCIETY, 2025)
The article examines the significance of our national folklore in the formation of the genre of description as a literary genre, the influence of Karakalpak epics as a literary oral source on the work of 19th-century poets, the connection between folklore and written literature, the study of descriptions, their features, and the artistic originality of authorial descriptions.